1638 A case of capturing changes in interatrial blood flow and anatomical structure during percutaneous PFO closure with platypnea orthodeoxia syndrome using intra-cardiac echocardiography. (17th January 2020) - Hashimoto, G; Ide, S; Hayama, H; Makino, K; Otsuka, T; Suzuki, M; Iijima, R; Hara, H; Moroi, M; Nakamura, M
Abstract: Background: Platypnea–orthodeoxia syndrome (POS) is an uncommon condition characterized by positional dyspnea and hypoxemia due to intracardiac right-to-left shunting through a patent foramen ovale (PFO). The most commonly associated conditions included pneumonectomy, ascending aortic dilation, and arch surgery, as previously reported. Percutaneous closure of PFO is useful treatment for POS. Case: A 76 year old man used home oxygen therapy because of unexplained hypoxemia. A decrease in blood oxygen saturation was observed in sitting and standing positions. The patient was diagnosed as "POS" because a shunt blood flow with PFO and atrial septal aneurysm (ASA) and eustachian valve was observed at transesophageal echocardiography. He was admitted for the purpose of percutaneous PFO closure. He was treated with intra-cardiac echocardiography (ICE) guidance under local anesthesia because of poor lung function. PFO closure was performed successfully with 30mm AMPLATZER Cribriform. The ICE findings prior to PFO closure showed a right-to-left shunt blood flow through the PFO in the sitting position but almost disappeared after closure. Furthermore, it was observed that the aortic artery compression was stronger in the sitting position than in the supine position with right-to-left shunt blood flow. After PFO closure, hypoxia associated with postural change improved and patient's symptom as shortness of breath also significantly improved. Discussion: POS is a position-dependent condition of dyspnea and hypoxemia due to right-to-left shunting. It often remains unrecognized in clinical practice, possibly because of its complex underlying pathophysiology. It is considered that the cause of POS in this patient was multiple factors such as ASA, aortic displacement, and venous valve remnant. In addition, being able to observe the change of the atrium due to compression from the aortic artery using ICE during the operation was very significant to explain the mechanism of POS.